(untitled) (Philological Studies, 2019)
The paper deals with the peculiarities of the way the modern Macedonian writers percept and artistically incarnate the geopolitical and cultural space of the country. The novels created in the 2000th which reflect the Balkanian’s certain mental changes under the conditions of the new century are being analyzed. The analysis concerns the following works – «The hub of the Universe» by V. Andonovsky (2000), «The ash tower» by L. Starova (2002), «The tunnel» by P.M. Andreevsky (2003), «The spectator» by J. Kuyundzhisky (2003). The area of the national life reproduced by the Macedonian novelists is presented as contradictory, being at the same time widely open and strictly closed. The authors keenly respond to the morbid problems of the modern society: inter-national conflicts, negligent attitude to the past, impoverishment of the morals, estrangement, and the loss of the vital reference points. The poetics of the Macedonian novel space in the works of the authors belonging to different generations is influenced by the complex social processes, connected with the problems of the Macedonian people’s selfidentification within the period of the second half of the XX century and under the conditions of globalization of the XXI century.